new species of Miogryllus Saussure, 1877 and new record of Miogryllus piracicabensis Piza, 1960 (Orthoptera: Gryllidae) from State of Rio Grande do Sul, Brazil, with calling song and chromosome complement - Orsini, Marcelo Pinheiro; Costa, Maria Kátia Matiotti Da; Szinwelski, Neucir; Martins, Luciano De Pinho; Corrêa, Robson Crepes; Timm, Vitor Falchi; Zefa, Edison (Zootaxa, 2017)
In this paper we describe a new species of Miogryllus cricket collected from the grasses at urban area of the municipality of Itaqui, State of Rio Grande do Sul, Brazil, highlighting phallic sclerites morphology, calling song parameters and chromosome complement. We also provide a new record for Miogryllus piracicabensis Piza, 1960 to the southern Brazil, improving calling song and karyotype information for this species. The type-material and vouchers are deposited in the Museu de Zoologia da Universidade de São Paulo (MZUSP).